Weight stigma and health behaviors: evidence from the Eating in America Study - Lee, Kristen M; Hunger, Jeffrey M; Tomiyama, A Janet (International Journal of Obesity, 2021)
Weight stigma is pervasive across the U.S. and is associated with poor health outcomes including all-cause mortality. One potential reason that weight stigma may be detrimental to health is that it begets poorer health behaviors. Therefore, the present study tested for associations between weight stigma and four health behaviors (i.e., eating behavior, alcohol use, sleep disturbance, and physical activity), while controlling for BMI and other potential confounds. Participants (N = 2022) in the U.S. were recruited for the Eating in America Study using a Qualtrics panel between December 2019 and January 2020 and were census-matched according to national quotas for age, gender, income, race/ethnicity, and census region. Participants completed questionnaires about weight stigma, health behaviors, demographics, and anthropometric measurements. The current study employed a two-stage investigation: exploratory analyses were first performed on a random sample of the dataset (n = 438), then the remaining unexamined data were used to conduct confirmatory analyses that were preregistered on the Open Science Framework. Controlling for BMI, weight stigma was significantly associated with greater disordered eating (b = 0.34, 95% CI [0.31, 0.38], p < 0.001), comfort eating (b = 0.32, 95% CI [0.25, 0.39], p < 0.001), sleep disturbance (b = 0.27, 95% CI [0.20, 0.33], p < 0.001), and alcohol use (b = 0.30, 95% CI [0.11, 0.49], p = 0.002), but not lower physical activity (b = -0.04, 95% CI [-0.13, 0.05], p = 0.402) for individuals across the weight spectrum. BMI and perceived weight status significantly moderated the effects of weight stigma on disordered eating and alcohol use. No gender differences were found. These confirmatory analyses partially replicated the exploratory stage 1 findings. This study provides preliminary evidence that weight stigma is linked to several poor health behaviors, which may impact physical health.